The Role of the Israel Defense Forces in Safeguarding National Security (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2025)
This paper explores the role of the Israel Defense Forces (IDF) as a key defense institution in safeguarding Israel’s national security following its conflict with Hamas, using defensive realism as the primary theoretical framework. This theory underscores the state’s priority in preserving security without seeking hegemonic power. Within this framework, the IDF is viewed as playing a crucial role in maintaining national integrity through military preparedness and air defense strategies, notably the deployment of the Iron Dome system to counter rocket threats from Hamas. The analysis also highlights the significance of defense diplomacy, particularly strategic cooperation with the United States, in enhancing the IDF’s operational capacity. By applying theoretical insights and case-based evidence, this paper demonstrates how the IDF effectively mitigates the impact of external threats and reinforces public security in a volatile post-conflict environment.